Out of Eastern Europe: Private Photography. - List Visual Arts Center - Massachusetts Institute of Technology, Cambridge (Cambridge : MIT Committee on the Visual Arts, 1987)
Bartonicek, Karel ; Caryk, Jerzy ; Demidowski, Lucjan ; Hajas, Tibor ; Halas, Istvan ; Kafka, Ivan ; Karolyi, Zsigmond ; Knizak, Milan ; Krejcar, Libor ; Novottny, Miklos ; Prüstel, Andreas ; Robakowski, Józef ; etc.
Out of Eastern Europe: Private Photography, List Visual Arts Center, Massachusetts Institute of Technology, Cambridge, January 17 - Aoril 12, 1987
boek
Keywords: Oost-Europa